A Christian View of Genetic Engineering (Global Journal of Human-Social Science, 2020)
There has been an age long conflict between religion and science Thus many scientific breakthroughs have literally faulted some religious claims In spite o f this the symbiotic relationship between the duo cannot be overlooked In o ther words there is a recurring scholarly intercourse and intellectual romance between science and religion as established by scholars This paper examines genetic engineer ing from a Chr istian perspective with emphasis on the prospect and burden of the innovation It is premised on Barbour s model for the study of the interaction between Religion and Science and Artigas Complementary Theory which emphasizes the harmonizing and dialoguing roles between science and religion Using content analysis this work delineates the blessing and woes of genetic engineer ing in the Christian context Christianity for instance balances respect for human life and dignity of the human person on the one hand and the blessings of science in human development on the other hand Whereas Christianity appreciates the fact of human creativity in genetic engineer ing as it leads to improved plant and animal lives increased food production and therapeutic functions it equally considers broad implications of this breakthrough on the human person future and his environment It is recommended that man must not lose his dignity nor should genetic engineers arrogate to themselves the Creator s right that is to determine what kind of human that should live or die Moreover religion as part of her oversight and prophetic function must be more proactive than reactive to current scientific progress in genetic engineering in order to guide and guard science from falling into the mash of conceited and self-destructive breakthroughs
Keywords: christianity; human person; plant and animal; science; DNA